2021
DOI: 10.1080/16070658.2021.1982499
|View full text |Cite
|
Sign up to set email alerts
|

The use of linear programming to determine whether breastfed infants can achieve a nutritionally adequate complementary feeding diet: a case study of 6–11-month-old infants from KwaMashu, KwaZulu-Natal, South Africa

Abstract: The objectives of this study were to ascertain whether the nutrient requirements of 6-11-month-old infants can be met with a food-based approach, and to identify the nutrients of which it is difficult to achieve adequate intakes. Design, setting and subjects: A cross-sectional survey and interviews with mothers and caregivers from the KwaMashu Community Health Centre were conducted. One hundred and thirty-four interviews were completed. This information provided the food consumption input for the model using O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The study aimed to ascertain whether the nutrient requirements of 6-11-month-old infants could be met with a food-based approach and to identify which nutrients from food were consumed in insufficient amounts. The results revealed that iron, zinc, and calcium were the nutrients that were not provided in sufficient amounts in the diet of infants from the study group [60]. Another study conducted by Chakona (2020) of 84 Eastern Cape mothers in their maternal and infant/young child dietary diversity and breastfeeding practices found that 56% of mothers perceived meal porridge as the type of food that should be given to a child for growth.…”
Section: Complementary Feeding Practices In South Africamentioning
confidence: 89%
“…The study aimed to ascertain whether the nutrient requirements of 6-11-month-old infants could be met with a food-based approach and to identify which nutrients from food were consumed in insufficient amounts. The results revealed that iron, zinc, and calcium were the nutrients that were not provided in sufficient amounts in the diet of infants from the study group [60]. Another study conducted by Chakona (2020) of 84 Eastern Cape mothers in their maternal and infant/young child dietary diversity and breastfeeding practices found that 56% of mothers perceived meal porridge as the type of food that should be given to a child for growth.…”
Section: Complementary Feeding Practices In South Africamentioning
confidence: 89%